Peran Dongeng Terhadap Sisa Makanan pada Siswa Sekolah Dasar Al - Irsyad Al – Islamiyyah Jember - Irfaul Hasanah; Muhammad Iqbal; Adhiningsih Yulianti Yulianti (HARENA : Jurnal Gizi, 2020)
The needs of school-age children, if noted more carefully, children spend a lot of energy while studying and doing activities. Fairy tales are fictitious forms of story that are told or written to entertain and contain values. Previous research has shown that listening to fairy tales has benefits that can increase children's creativity and imaginative power. The general objective of this research is to be able to find out the role of fairy tales on leftovers in Al-Irsyad Al-Islamiyyah Jember elementary school students. This type of research is an experimental Quasi research with a one group pre-test and post-test approach. The subjects in this study were grade II students of Al-Irsyad Al-Islamiyyah Jember Elementary School with a total of 42 respondents. The rest of the data collection is done by estimation using Comstock form while the media used is a fairy books. Data results were analyzed using Wilcoxon test due to undistribution of normal data. The average of the rest of the food occurs despite the decline not all significant. The remaining staple food before the intervention was 33.81% while after an intervention of 23.33% with a difference of 10.48 (P = 0.14), the rest of the animal side dishes before the intervention 22.14% after the intervention of 16.55% with the difference of 5.59 (P = 0.43), the rest of the vegetable side dishes 49.40 Before the intervention and after the intervention was 30.36% with the difference of 19.04 (P = 0.09). The remaining vegetable before the intervention was 58.81% and after an intervention of 24.40% (P = 0.01) with a difference of 34.41. There are no significant differences in fairy tales against the rest of staple food, animal side dishes and vegetable side dishes. There are significant differences in fairy tales against leftover vegetable food